Effect bulking agent on composting mexican sunflower (Tithonia diversifolia L) biomass and utilization on pak choi production - Jahra Pelu; Setyono Y. Tyasmoro; Moch. Dawam Maghfoer (Fakultas Pertanian Universitas Yudharta Pasuruan, 2020)
Mexican sunflower or paitan in Indonesian (Thitonia diversifolia L) is a weed with high biomass production with nutrient quality that potentially use as composting material. However, there were problem for for optimize composting process due to low C/N ratio and high moisture content of this material. Therefore co-composting with higher C/N ratio and low moisture bulking materials to attain a proper composting process. Research to (1) Evaluate the effect of raw rice husk (RRH) and rice husk charcoal (RHC) as bulking agent on quality of compost T.diversifolia. Two composting mixture were TRRH = biomass T. Diversifolia + raw rice husk and TRHC = T. diversifolia biomass + rice husk biochar. Data were analyzed descriptively and compared with National Standards of Organic Fertilizer SNI 19-7030-2004. (2) To Compare the effect TRRH and TRHC compost on growth and yield of pakchoi (Brassica rapa var chinensis). Plant height, number of leaves, leaf area, edible and total fresh weight and N uptake analyzed with ANOVA and mean diference with Tukey/HSD test. The results showed that (1) T.diversifolia L compost has nutritional quality of N, P, K in accordance with SNI 19-7030-2004, but the levels of N, P and K in TRHC > TRRH. (2) TTRH.40 planting media gave maximum growth and yield of pakchoy compared to other treatments. The study confirms that composting T.diversifolia L biomass were potential to enhance pakchoi production while promoting cultivation of vegetables for food security.